2022
DOI: 10.1093/icvts/ivac256
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation in patients with a history of anatomical native lung resection

Abstract: OBJECTIVES History of anatomical lung resection complicates lung transplantation (LTx). Our aim was to identify indications, intraoperative approach, and outcome in these challenging cases in a retrospective multicentre cohort analysis. METHODS Members of the ESTS Lung Transplantation Working Group were invited to submit data on patients undergoing LTx after a previous anatomical native lung resection between 01/2005 and 07/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, a multi-center, retrospective analysis from the LTx working group of the European Society of Thoracic Surgeons analysed 2,690 LTx patients between 2005 and 2020, of which 26 had a previous history of anatomical lung resection by open approach. Survival of these patients seemed comparable to conventional LTx patients, thereby indicating that a history of previous thoracic surgery is not an absolute contraindication ( 16 ). In this study, we did not find that the use of clamshell or ECLS during the primary LTx is a prerequisite to use the same approach in re-LTx.…”
Section: Discussionmentioning
confidence: 84%
“…However, a multi-center, retrospective analysis from the LTx working group of the European Society of Thoracic Surgeons analysed 2,690 LTx patients between 2005 and 2020, of which 26 had a previous history of anatomical lung resection by open approach. Survival of these patients seemed comparable to conventional LTx patients, thereby indicating that a history of previous thoracic surgery is not an absolute contraindication ( 16 ). In this study, we did not find that the use of clamshell or ECLS during the primary LTx is a prerequisite to use the same approach in re-LTx.…”
Section: Discussionmentioning
confidence: 84%
“… 2 , 3 Contrary to these reports, a recent study by the European Society of Thoracic Surgery Lung Transplantation Working Group claims that any history of anatomic lung resection, including pneumonectomy, results in similar outcomes to conventional lung transplantation. 4 However, the authors here described a small population of patients and included only 2 cases of previous contralateral pneumonectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the lung allocation score (LAS) has resulted in an increase in the average age of patients undergoing LTX, and, consequently, an increase in the diagnosis of pre-LTX neoplasia [5]. Despite these current uncertainties, several studies have shown that LTX can be a valid therapeutic option even for patients with a history of oncological disease, as long as specific selection criteria are met and a careful post-transplant monitoring is performed [6][7][8]. The rate of neoplastic recurrence after LTX ranges from 0 to 57%, with the majority reported within the first 5 years post LTX [9].…”
Section: Introductionmentioning
confidence: 99%